Reflections on the Decreasing Affordability of Legal Education - Jerome M. Organ (Washington University Journal of Law & Policy, 2013)
This Article offers two different lenses for thinking about the “affordability” of legal education. Part I discusses a historical perspective focused on aggregated data over time: average tuition in relation to average salaries of law school graduates. Part II discusses a present day perspective, estimating the percentage of Class of 2011 graduates for whom legal education might be considered affordable using a formula drawing on debt-to-income ratios associated with mortgages. Part III discusses the extent to which affordability may vary among public and private law schools, law schools in different states or regions, and for students with different LSAT and GPA profiles. Part IV concludes with a discussion of some of the challenges legal education will face as a result of legal education’s decreasing affordability.
Keywords: legal education; law school tuition; affordability of legal education; legal salaries